Pengaruh Rasio Likuiditas Dan Profitabilitas Terhadap Kinerja keuangan pada Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Yang Terdaftar Di Bei Periode 2019 - 2023 - Widia Ningsih (GLOBAL SCIENTS PUBLISHER, 2024)
This research aims to evaluate the influence of liquidity ratios (Current Ratio) and profitability (Net Profit Margin) on the financial performance (Return on Assets) of food and beverage subsector manufacturing companies on the Indonesia Stock Exchange during the 2019-2023 period. The research method uses a quantitative approach with descriptive statistical analysis and multiple regression. The results of this research show that the effect of the liquidity ratio on the company's financial performance was found to be significant (β = 0.361, p < 0.05), as was the profitability ratio (β = 0.669, p < 0.05). Regression analysis shows that the two independent variables are able to explain 77.6% of the variation in the company's financial performance (Adjusted R Square = 0.776). In addition, the simultaneous F test shows that the influence of the two independent variables simultaneously is also significant (F = 150.213, p < 0.05), validating the third hypothesis (H3) that liquidity and profitability ratios jointly contribute to the company's financial performance.